2015
DOI: 10.1002/rcm.7396
|View full text |Cite
|
Sign up to set email alerts
|

Urea and lipid extraction treatment effects on δ15N and δ13C values in pelagic sharks

Abstract: Given the mean change in δ(15)N(1.2 ± 0.6‰) and δ(13)C values (0.7 ± 0.4‰) across pelagic shark species, it is recommended that muscle tissue samples be treated with LE+DW to efficiently extract both urea and lipids to standardize isotopic values. Mathematical normalization of urea and lipid-extracted δ(15)N(LE+DW) and δ(13)C(LE+DW) values using the lipid-extracted δ(15)N(LE) and δ(13)C(LE) data were established for all pelagic shark species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
81
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 48 publications
16
81
2
Order By: Relevance
“…Thus, high urea concentrations in elasmobranch tissues lower δ 15 N values, and this can result in an underestimation of trophic positions (Kim and Koch ; Carlisle et al ). Experimental studies examining the influence of urea on elasmobranch δ 15 N have illustrated that urea‐extracted tissues generally have higher δ 15 N and C:N ratios relative to untreated tissues although results are not consistent across all species (Kim and Koch ; Li et al ; Burgess and Bennett ; Carlisle et al ). The increase in C:N ratio following urea‐extraction has important implications for assessing tissue lipid content based on the C:N ratios.…”
mentioning
confidence: 99%
“…Thus, high urea concentrations in elasmobranch tissues lower δ 15 N values, and this can result in an underestimation of trophic positions (Kim and Koch ; Carlisle et al ). Experimental studies examining the influence of urea on elasmobranch δ 15 N have illustrated that urea‐extracted tissues generally have higher δ 15 N and C:N ratios relative to untreated tissues although results are not consistent across all species (Kim and Koch ; Li et al ; Burgess and Bennett ; Carlisle et al ). The increase in C:N ratio following urea‐extraction has important implications for assessing tissue lipid content based on the C:N ratios.…”
mentioning
confidence: 99%
“…Recently, Matley et al (2016) showed that diet tissue determination factors and turnover rates measured for temperate species may not apply to tropical species, as δ 15 N enrichment was lower than published values for a slowgrowing predatory reef fish. In larger predatory species such as sharks, care in sample preparation is also necessary as urea retention without extraction can severely affect values, which is often not a common method employed for stable isotope analysis (Li et al, 2016). The physical and biogeochemical nature of a habitat can also have large effects on trophic community structure even at a fine scale.…”
Section: Biochemical Tracersmentioning
confidence: 99%
“…Dermis was then freeze-dried at −55°C for 48 h using a Christ Alpha 1-4 LD plus Freeze Dryer (Martin Christ), and each sample was homogenized using a Retsch Mixer Mill MM 400 (Retsch). Sharks maintain urea and trimethyl amine oxide in their tissues for osmotic balance, which are considered to be 15 N-depleted and may also affect δ 13 C values (Fisk et al 2002, Li et al 2016. Consequently, urea was removed from muscle tissue using a standard water washing technique (Kim & Koch 2012, Li et al 2016).…”
Section: Stable Isotope Analysismentioning
confidence: 99%
“…Sharks maintain urea and trimethyl amine oxide in their tissues for osmotic balance, which are considered to be 15 N-depleted and may also affect δ 13 C values (Fisk et al 2002, Li et al 2016. Consequently, urea was removed from muscle tissue using a standard water washing technique (Kim & Koch 2012, Li et al 2016). For δ 15 N analysis, all muscle tissue samples were urea-extracted, while for δ 13 C, both urea and lipids were removed using combined water washing and standard chloroformmethanol extraction (Li et al 2016).…”
Section: Stable Isotope Analysismentioning
confidence: 99%
See 1 more Smart Citation